Evaluation of the Implementation of Occupational Health and Safety Management System on the Renovation Construction Project of Grand Inna Malioboro Hotel, Yogyakarta City - Ashari Rhomadon; Dyah Suryani; Widodo Hariyono (Jurnal EduHealth, 2025)
The construction industry is inherently high-risk, making Occupational Health and Safety (OHS) a critical priority. This study evaluates the implementation of the Occupational Health and Safety Management System (OHSMS) in the renovation project of Grand Inna Malioboro Hotel, located in a densely populated tourism area of Yogyakarta City. The project’s urban setting introduces additional challenges in ensuring safety for both workers and the surrounding public. A qualitative descriptive approach with a case study method was employed. Data were collected through in-depth interviews with project stakeholders, direct field observations, and a review of project documents including the Safety Plan (RK3K), incident reports, and training attendance records. The collected data were analyzed using the SWOT framework (Strengths, Weaknesses, Opportunities, Threats). Findings indicate that while OHSMS documentation and personnel are in place, the on-site implementation is inconsistent. Strengths include management support, the presence of a safety officer, and regular briefings. However, weaknesses persist, such as incomplete safety training, weak subcontractor oversight, and inadequate incident reporting. The project has opportunities for improvement through regulatory support and public visibility, but also faces threats due to its location in a high-traffic urban area. This study concludes that while the OHSMS has been formally adopted, its practical implementation needs enhancement through better training, consistent supervision, and broader stakeholder involvement. Regular evaluation and integrated safety strategies are essential to strengthening safety culture in similar renovation projects, particularly those in complex urban environments.